SWEETENER FORMULATION FOR MAKING JAM SHEETS COMBINATION OF PINEAPPLE (Ananas comosus L. Merr) AND GREEN MUSTARD (Brassica juncea L.) - Stephanie, Akuilla; Lestari, Oke Anandika; Priyono, Suko (Universitas Trilogi, 2025)
Pineapple and green mustard are fruits and vegetables that have the potential to be processed into jam sheets. Sweetener is one of the components used in jam making. This study aims to obtain the best sweetener formulation on the physicochemical characteristics and organoleptic properties of pineapple-cabbage jam. The research was conducted using the Randomized Group Design (RAK) method with 1 (one) research factor, namely the concentration of sucrose, honey, and stevia sweeteners. The variables observed were water content, total acid, color, reducing sugar and organoleptic test. The resulting data were analyzed by ANOVA test and if the data had a significant effect, the BNJ further test was carried out at the 5% level. The best treatment in the research of pineapple-cabbage sheet jam was found in the sweetener treatment with a ratio of 50% sucrose, 37.5% honey, and 12.5% stevia. Pineapple mustard sheet jam with various formulations of sucrose, honey, and stevia sweeteners influenced the moisture content, total acid, reducing sugar, color, and sensory properties in the form of color, texture, and sweetness.